Clinicopathological analysis of biliary neuroendocrine neoplasms and chemotherapy for biliary neuroendocrine carcinoma - Sasahira, Naoki; Sasaki, Takashi; Takamatsu, Manabu; Mie, Takafumi; Ozaka, Masato; Takeda, Tsuyoshi; Matsuyama, Masato; Furukawa, Takaaki; Kasuga, Akiyoshi (Tando, 2020)
Biliary neuroendocrine neoplasms (NENs) are very rare. Seventeen biliary NENs were analyzed in this study. The major primary sites were gallbladder and papilla of Vater. NENs of the gallbladder were more common in women, and those of the papilla of Vater were in men. Six of the seven gallbladder NENs were neuroendocrine carcinomas (NECs). Among 10 surgical resected cases, all 7 cases except NET-G1 recurred, and the most of the recurrence was appeared in the liver. The treatment outcomes of cisplatin and irinotecan combination therapy for 11 biliary NECs were relatively good with a response rate of 72.7%, a disease control rate of 90.9%, a median progression-free survival of 7.9 months, and a median overall survival of 12.0 months. Major adverse events of grade 3 or higher included leukopenia (45.5%), neutropenia (63.6%), and anemia (27.3%). The combination therapy of cisplatin and irinotecan was feasible and showed a relatively good efficacy for biliary NECs.